The Performance of Domestic Wastewater Sludge –Sawdust Clay Bricks. - Tukwatsiibwe, Ivan (Kabale University, 2023)
Wastewater sludge is a by-product left over from the wastewater treatment process. The sludge presents an increasingly difficult problem to cities of all sizes because of the scarcity of suitable disposal sites, increasing labour costs, and environmental concerns. The study investigated the use of domestic wastewater sludge incorporated with clay and sawdust. In this study, bricks were produced with domestic wastewater sludge additions ranging from 0-55 % by volume respectively and wood sawdust and compared the produced brick with regular brick. The compressive strength for convectional brick was found to be 6.6% and that of the three mixtures was found to be increasing with increasing percentages of sludge and wood sawdust.